Law and Justice for Development - World Bank (Weltbankgruppe: The World Bank legal review;, 2003)
Sustainable poverty reduction and equitable economic development depend on the solid foundation of the rule of law. These reforms are underpinned by legal reform, whether it be to increase efficiency in business transactions, benefit from globalization policies, improve the way governments deliver essential services, or facilitate access to a more efficient and effective justice system. Internationally, rules and frameworks of cooperation are required in order to confront new global threats, such as communicable diseases, attacks on the environmental commons, destabilizing capital movements, and money laundering. The World Bank Legal Review, the first in a new annual series, offers a combination of legal scholarship, lessons from experience, legal developments, and recent reports on the many ways in which the application of law and the improvement of justice systems promote poverty reduction, economic development, and the rule of law. This book, produced by the Legal Vice Presidency of the World Bank, is a publication for policymakers and their legal advisers, attorneys and other professionals involved in the area of international development